New insights into the evolutionary characteristic between the New World and Old World Lupinus species using complete chloroplast genomes. Issue 1 (1st January 2021) - Tang, Yiwang; Zhao, Yunlin; Li, Chaoyang; Yang, Guiyan; Peng, Jiao; Xu, Zhenggang
Abstract : Lupinus is one of the most geographically widespread genera. It can be divided into New World and Old World Lupinus species according to the geographical distribution of its members. However, there are relatively few studies on their genetic differences, especially regarding the taxonomy and geographical evolutionary history of New World species. Here, we conducted comparative, phylogenetic, and evolution analysis between one New World and five Old World Lupinus species based on their complete chloroplast genomes. Compared with the Old World species, the chloroplast genome of L. westianus in the New World was more variable, showing the deletion of the pseudogene ycf1 and two rps12 gene introns, the 20 kb inversion, the higher number of repeated sequences, the larger genome size, and the lower GC content. Phylogenetic analysis indicated that the genetic relationship between the New World species L. westianus and the Old World species L. albus was closer than to the rest. Evolutionary analysis confirmed that the matK and ycf1 genes were under positive selection, and rpoA, accD, and rpoC2 genes have site-specific selection in L. westianus, which might be related to adaptive evolution. Therefore, our finding would provide genetic information for the evolutionary history and taxonomy of Lupinus species.